Monetary Policy, Inflation, and Distributional Impact : South Africa's Case - Miyajima, Ken (IMF Working Papers; Working Paper, 2021)
The South African Reserve Bank has continued to fulfill its constitutional mandate to protect the value of the local currency by keeping inflation low and steady. This paper provides evidence that monetary policy tightening aimed at maintaining low and stable inflation could at the same time reduce consumption inequality over a 12-18 month horizon, commonly understood as the transmission lag of monetary policy action to the real economy, and similar to the distance between survey waves used in the analysis. In response to 'exogenous' monetary policy tightening, the real consumption of individuals at lower ends of the consumption distribution declines relatively modestly, or even increases. With greater reliance on government transfers, thus smaller reliance on labor income, and relatively larger food consumption, these individuals appear to benefit mainly from lower inflation. By contrast, the real consumption of individuals at higher ends of the consumption distribution is more likely to decline due to lower labor income, weaker asset price performance, and higher debt service cost.